2005
DOI: 10.1158/0008-5472.can-04-4297
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cellular Proliferation in Tumor and Normal Tissues of Patients with Breast Cancer by [18F]Fluorothymidine-Positron Emission Tomography Imaging: Evaluation of Analytical Methods

Abstract: There is an unmet need to develop imaging methods for the early and objective assessment of breast tumors to therapy. 18 F]FLT (K i ) ranged from 0.6 to 10.4 Â 10 À4 and from 0 to 0.6 Â 10 À4 mL plasma cleared/s/mL tissue in tumor (29 regions, 15 patients) and normal tissues, respectively. Tumor K i and fractional retention of radiotracer determined by spectral analysis correlated with Ki-67 labeling index (r = 0.92, P < 0.0001 and r = 0.92, P < 0.0001, respectively). These correlations were superior to those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
151
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(154 citation statements)
references
References 33 publications
2
151
0
1
Order By: Relevance
“…NLR3k-derived K i , Patlak-derived K i , SUV 41% and SUV max showed excellent reproducibility with ICCs of 0.92, 0.95, 0.98 and 0.93, and SDs of 16%, 12%, 7% and 11%, respectively (Table 2). In contrast, NLR3k-derived k 3 , which, at least in theory, selectively reflects TK1 activity, showed poor reproducibility with an ICC of 0.43 and an SD of 38%. As expected from Akaike and Schwarz analyses, inclusion of a fourth rate constant resulted in decreased reproducibility with an ICC of 0.75 and an SD of 25% for NLR4k-derived K i , and an ICC of 0.33 and an SD of 70% for NLR4k-derived k 3 ( Table 2).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…NLR3k-derived K i , Patlak-derived K i , SUV 41% and SUV max showed excellent reproducibility with ICCs of 0.92, 0.95, 0.98 and 0.93, and SDs of 16%, 12%, 7% and 11%, respectively (Table 2). In contrast, NLR3k-derived k 3 , which, at least in theory, selectively reflects TK1 activity, showed poor reproducibility with an ICC of 0.43 and an SD of 38%. As expected from Akaike and Schwarz analyses, inclusion of a fourth rate constant resulted in decreased reproducibility with an ICC of 0.75 and an SD of 25% for NLR4k-derived K i , and an ICC of 0.33 and an SD of 70% for NLR4k-derived k 3 ( Table 2).…”
Section: Resultsmentioning
confidence: 90%
“…Several studies have shown good correlations between [ 18 F]FLT uptake and other markers of cellular proliferation, including proliferating cell nuclear antigen, flow cytometry and Ki-67 nuclear staining [1][2][3][4][5].…”
mentioning
confidence: 99%
“…In contrast to thymidine, FLT is poorly incorporated into DNA (Sundseth et al, 1996). 3 0 -deoxy-3 0 -[ 18 F]fluorothymidine uptake is correlated with S-phase (Rasey et al, 2002), Ki67 immunostaining (Kenny et al, 2005) and TK-1 levels (Barthel et al, 2005). As, anticancer treatment can inhibit proliferation it may change FLT uptake, implying a role for FLT as a marker for monitoring response to chemotherapy.…”
mentioning
confidence: 99%
“…12 Therefore, FLT is considered to be a proliferation marker and, as such, could be a more specific tracer of tumor "activity". Indeed, correlations between FLT uptake and S-phase, 12 Ki-67 immunostaining 13 and TK-1 levels 14 have been reported.…”
Section: Research Papermentioning
confidence: 98%